Pelvic Compensation in Sagittal Malalignment: How Much Retroversion Can the Pelvis Accommodate?. Issue 4 (15th February 2020) - Beyer, George; Khalifé, Marc; Lafage, Renaud; Yang, Jingyan; Elysee, Jonathan; Frangella, Nicholas; Steinmetz, Leah; Ge, David; Varlotta, Christopher; Stekas, Nicholas; Manning, Jordan; Protopsaltis, Themistocles; et al.
Abstract : Study Design: Single-center retrospective study. Objective: Investigate how differing degrees of pelvic incidence (PI) modulate the recruitment of pelvic tilt (PT) in response to similar amounts of sagittal malalignment as measured by T1-Pelvic Angle (TPA). Summary of Background Data: Past research has shown that some patients do not recruit PT in response to sagittal malalignment. Given the anatomic relationship between PI and PT, we sought to determine whether differing PI is associated with variable recruitment of PT. Methods: Single-center retrospective study of 2077 patients undergoing full body radiographs and TPA>10°. Five groups of patients (Very Low, Low, Average, High, and Very High PI) were defined utilizing PI ranges on a Gaussian distribution. Linear regression (LR) evaluated correlation of TPA to PT within each PI group. Multivariate LR evaluated whether correlation between TPA and PT differed between each PI group. Results: Mean PT increased with increasing levels of PI ( P  < 0.05). Within the full cohort, PT correlated with TPA (r = 0.80, P  < 0.001). Multivariate LR revealed significant differences between slopes and intercepts of the linear relationship between PT and TPA within the PI groups. Compared with patients with an average PI, patients with Very Low PI had 3.4° lower PT while holding TPA constant ( P  < 0.001). Further, patients with Very High PI displayed a PT of 1.9° higher than patients with an Average PI while holding TPA constant ( P  = 0.01). A similar difference of −1.8°, and 1.2° with respect to the Average PI group was observed in the Low and High PI groups, respectively ( P  < 0.001). Means and standard deviations of PT at varying levels of TPA were defined for PI groups. Conclusion: This is the first study which demonstrated that PI is associated with varied recruitment of PT while maintaining constant sagittal malalignment. The results reported herein are intended to allow surgeons to assess a patient's magnitude of compensatory PT for an individual patient's PI. Level of Evidence: 3 Abstract : There remains little information concerning the assessment and characterization of compensatory mechanisms within the spinal deformity population. We demonstrate the relationship between sagittal malalignment and pelvic tilt at varying magnitudes of pelvic incidence to determine whether pelvic anatomic variation portends varying degrees of physiologic compensation in response to sagittal malalignment.